Aguinaldo garagoense: descripción de las transformaciones identitarias en su evento inaugural y personaje festivo principal - Vega Gordillo, Karen Daniela (Universidad Antonio Nariño, 2024)
The thesis focuses on the Aguinaldo Garagoense, a traditional celebration deeply rooted in the municipality of Garagoa, Boyacá. It has been passed down through generations and has become a fundamental element of the cultural identity of the community during the December holidays. Despite its long history, there is a noticeable lack of accurate documentation regarding the origins of this celebration, making its study and preservation essential.